2016
DOI: 10.1186/s12858-016-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of GGCT inhibits cell proliferation and induces late apoptosis in human gastric cancer

Abstract: BackgroundGamma glutamylcyclotransferase (GGCT) has been proved to be involved in various cancers, but the biological function of GGCT in gastric cancer is still largely unknown. MethodsThe expression level of GGCT was evaluated by informatics analyses based on the Oncomine database. GGCT gene was then effectively knocked down via lentivirus mediated short hairpin RNA (shRNA) system. Then a series of functional assays, including MTT, colony formation and flow cytometry analysis were conducted on gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
19
0
1
Order By: Relevance
“…Moreover, studies have shown that apoptotic resistance promote cell proliferation . Apoptotic event exists both in early apoptosis and late apoptosis of cell cycle duration; DNA double strand irreversibly breaks and loses its function in late phase apoptosis . We indicated that fractalkine's molecular function on late phase apoptosis is crucial for promoting cell proliferation in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, studies have shown that apoptotic resistance promote cell proliferation . Apoptotic event exists both in early apoptosis and late apoptosis of cell cycle duration; DNA double strand irreversibly breaks and loses its function in late phase apoptosis . We indicated that fractalkine's molecular function on late phase apoptosis is crucial for promoting cell proliferation in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 90%
“…Ggct is an enzyme that plays a role in glutathione degradation (Oakley et al, 2008 ) and has been shown to be a contributor to a variety of cancers (reviewed in Zhang et al, 2016 ). Importantly, Ggct has been recently shown to play a role in cell proliferation and death, implicated by Ggct knockdown experiments that resulted in an inhibition of proliferation and an induction of apoptosis in human cancer cells (Zhang et al, 2016 ). Ggct has no known role in retinal development, but it is present in the developing and mature retina where it is most heavily distributed to the IPL and outer portion of the INL, where the RBC population is present (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which Ggct could alter RBC number remains unknown. Ggct is upregulated in many human cancers and therefore has been postulated to modulate both apoptotic and cell proliferation pathways (Zhang et al, 2016 ). For example, when GGCT was silenced in cultured colorectal cancer cells, it was sufficient to trigger caspase-3-mediated apoptosis (Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-Y and Sp1 bind to the CCAAT boxes and to the GC box, respectively, to positively regulate transcription of the GGCT gene. Since promoters with several NF-Y-binding CCAAT boxes were found in genes related to the cell cycle, Ohno et al suggested that GGCT may also play a role in the cell cycle [ 18 ], as confirmed by other studies [ 19 , 20 , 21 , 22 ].…”
Section: Molecular Regulation Mechanism Of Ggct Expression In Cancmentioning
confidence: 86%